2003
DOI: 10.1034/j.1600-0560.2003.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous pseudolymphoma in association with molluscum contagiosum in an elderly patient

Abstract: After ruling out systemic involvement, the patient was followed up for 2 years with no evidence of recurrence. We report this case to the best of our knowledge and discuss the literature about atypical clinical and histological presentations of MC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 10 publications
(16 reference statements)
0
31
0
Order By: Relevance
“…Primary cutaneous CD30+ positive lymphoproliferative T-cell disorders represent a spectrum ranging from lymphomatoid papulosis to anaplastic large cell lymphoma. 40 Recently, CD30 expression was described on variable numbers of cells in several benign dermatoses such as carbamazepine-28 and cefuroxime-induced 33 drug reactions, scabies, 16,24 gold acupuncture reactions, 20 atopic dermatitis, 15 verruca vulgaris, 11 molluscum contagiosum, 27 Milker's nodule, 32 and various other nonneoplastic cutaneous infiltrates, 6 including also cutaneous herpetic infections. 13 In our cases, CD30 positivity was observed in scattered atypical lymphocytes with large, hyperchromatic nuclei, unlike the clustered CD30+ atypical cells found in lymphomatoid papulosis.…”
Section: Discussionmentioning
confidence: 99%
“…Primary cutaneous CD30+ positive lymphoproliferative T-cell disorders represent a spectrum ranging from lymphomatoid papulosis to anaplastic large cell lymphoma. 40 Recently, CD30 expression was described on variable numbers of cells in several benign dermatoses such as carbamazepine-28 and cefuroxime-induced 33 drug reactions, scabies, 16,24 gold acupuncture reactions, 20 atopic dermatitis, 15 verruca vulgaris, 11 molluscum contagiosum, 27 Milker's nodule, 32 and various other nonneoplastic cutaneous infiltrates, 6 including also cutaneous herpetic infections. 13 In our cases, CD30 positivity was observed in scattered atypical lymphocytes with large, hyperchromatic nuclei, unlike the clustered CD30+ atypical cells found in lymphomatoid papulosis.…”
Section: Discussionmentioning
confidence: 99%
“…A single case report of skin nodule and EU-like lesion showing identical monoclonal TCR-γ gene rearrangement has been reported and accordingly the oral lesion is regarded as CD30+ T cell non-Hodgkin’s lymphoma (lymphomatoid papulosis). As large atypical CD30+ cells have been reported in a variety of conditions such as infections [40], parasitic [41] and inflammatory disorders [42], their presence in EU is regarded as a reactive process to yet undetermined antigen(s). …”
Section: Discussion and Reviewmentioning
confidence: 99%
“…In rare instances, a delayed hypersensitivity response to the MC virus can trigger an intense infiltrate of atypical lymphocytes mimicking a lymphoma. 5 Flame figures have also been reported in conjunction with MC. 10 Initially described in Wells syndrome and typically seen in bullous pemphigoid, eczema, and urticaria, flame figures consist of dermal collagen fibers coated with eosinophilic granules, most likely representing a hypersensitivity response.…”
Section: Discussionmentioning
confidence: 85%
“…The lack of inflammatory response typical of MC is partly attributable to the lipid encasement surrounding the molluscum bodies. 5 In addition to the banal presentation of MC, pseudocystic, polypoid, and giant MC variants have been described. 6 It has been reported that up to 4% of MC cases have been seen in association with other lesions.…”
Section: Discussionmentioning
confidence: 98%